10th East international : selectors : Keith Piper, Sebastian Lopez. - Art in Ruins; Morris, Lynda (Norwich : Norwich University of the Arts, 2000)
Piper, Keith ; Lopez, Sebastian ; Ajamu ; Andrini, Alessandra ; Desjardin, Arnaud ; Art in Ruins ; Fan, Brendan ; Jaycock, Carl ; Stewart, Christopher ; Tan, Erika ; Palmer, Eugene ; Goodman, Frances ; Offeh, Harold ; Locke, Hew ; Al-Ani, Jananne ; Thompson, Keith ; Douglas, Lorrice ; Lowenstein, Lyn ; Chauda, Meera ; Gaba, Meschac ; Wong, Ming ; Conroy, Neil ; Sanderson, Lesley ; Zangrillo, Peter ; Garfield, Rachel ; Illingworth, Shana ; Tegala, Simon ; Stuby, Tamara ; Chance, Veronique ; van Oldenborgh, Wendelien ; Doig, Peter ; Arden, Roy ; Charlton, Alan ; Durand-Dessert, Michel ; Logsdail, Nicholas ; Dean, Tacita ; Long, Richard ; Ackling, Roger ; Goodman, Marian ; Penone, Giuseppe ; Dibbets, Jan ; Tremlett, David ; Chadwick, Helen ; Allthorpe-Guyton, Marjorie ; Brighton, Andrew ; Moffat, Sandy
Engels
10th East international: selectors : Keith Piper, Sebastian Lopez, Norwich Gallery - Norwich School of Art and Design, Norwich, 15 July to 26 August 2000
boek